Reconstructing the Humanitarian Paradigm in Islamic Education - Kenedi, Gusril; Zalnur, Muhammad; Rosdialena (Tarbawiyah Jurnal Ilmiah Pendidikan, 2024)
The humanitarian paradigm in Islamic education is a pattern or outlook on human education. In essence, Islamic education views humans as creatures who need to get guidance, in this case, of course, education. Therefore, Islamic education aims to glorify human humanity and is based on the humanity that humans possess. Because human humanity will not be able to develop without educational services. This type of research is library research or literature study, namely research that focuses on literature studies by analyzing existing literature collections related to this research, both from primary and secondary sources. The purpose of this research is to understand the importance of Islamic education in order to realize a complete human being in accordance with the potential possessed both physically and spiritually in order to create a harmonious relationship for each individual with the Creator, humans and the universe. The results of this study indicate that by understanding the humanitarian paradigm in Islamic education, it is hoped that educators can advance Islamic education to the fullest. If there are technical problems, an evaluation can be carried out and if there are problems in the process, psychology and Islamic education counseling can help.